Coronary Arteriographic Profile in Hypertrophic Cardiomyopathy (HCM) - Hasan, Iqbal; Haque, KMHSS; Ahmed, Shaffiuddin; Siddique, MA; Banerjee, SK; Ahasan, SA; Ahamed, CM; Abdullah, ABM; Salim, MA; Rahman, MA; Siddiqui, KN (Nepalese Heart Journal, 2004)
This cross-sectional study was carried out in department of cardiology, Combined Military Hospital, Dhaka, Bangladesh and department of cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh during the period of April 2000 to November 2001. The study was designed to see the coronary arteriographic (CAG) pattern in patients with Hypertrophic Cardiomyopathy and to compare the CAG findings between HCM patients and normal coronary patients, HCM was diagnosed by using diagnostic criteria defined by Western Working Group. The patients with hypertention, congenital heart disease, valvular heart disease, coronary artery disease were excluded from the study. Among total 60 subjects, 30 had HCM and 30 age and sex matched control. The mean age of cases was 45.00±15.38 years and control subjects was 44.35±15.14 years. HCM cases had significantly higher left ventricular systolic pressure, higher left ventricular end diastolic pressure and more ejection fraction than control. Origin of coronary artery both in control and HCM cases were normal.